2019
DOI: 10.3390/genes10110866
|View full text |Cite
|
Sign up to set email alerts
|

To Repeat or Not to Repeat: Repetitive Sequences Regulate Genome Stability in Candida albicans

Abstract: Genome instability often leads to cell death but can also give rise to innovative genotypic and phenotypic variation through mutation and structural rearrangements. Repetitive sequences and chromatin architecture in particular are critical modulators of recombination and mutability. In Candida albicans, four major classes of repeats exist in the genome: telomeres, subtelomeres, the major repeat sequence (MRS), and the ribosomal DNA (rDNA) locus. Characterization of these loci has revealed how their structure c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 102 publications
(134 reference statements)
0
25
0
Order By: Relevance
“…Although intrachromosomal rearrangements are considered as one of the most prominent adaptation mechanisms [67][68][69], this type of rearrangement does not explain the great difference in terms of the number of species between Passeriformes and Psittaciformes, since both orders underwent a similar amount of intrachromosomal changes. Repetitive DNA plays an important role in genome organization and function, and they often serve as hotspots of genome rearrangements [31,32]. Hence, by comparing the chromosomal mapping of microsatellite sequences between the sister clades Passeriformes and Psittaciformes, with low and high rates of chromosomal rearrangements, respectively, we can speculate about the importance of these sequence in the karyotype reorganization and the diversification of these clades.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although intrachromosomal rearrangements are considered as one of the most prominent adaptation mechanisms [67][68][69], this type of rearrangement does not explain the great difference in terms of the number of species between Passeriformes and Psittaciformes, since both orders underwent a similar amount of intrachromosomal changes. Repetitive DNA plays an important role in genome organization and function, and they often serve as hotspots of genome rearrangements [31,32]. Hence, by comparing the chromosomal mapping of microsatellite sequences between the sister clades Passeriformes and Psittaciformes, with low and high rates of chromosomal rearrangements, respectively, we can speculate about the importance of these sequence in the karyotype reorganization and the diversification of these clades.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, only four Passeriformes species (P. tapera, P. chalybea, P. cyanoleuca, and S. flaveola) and two Psittaciformes ones (Myiopsitta monachus and Amazona aestiva) have been analyzed with chromosomal mapping of SSRs sequences [36,38] (Table 1). Comparing the three SSRs used in common in Repetitive DNA plays an important role in genome organization and function, and they often serve as hotspots of genome rearrangements [31,32]. Hence, by comparing the chromosomal mapping of microsatellite sequences between the sister clades Passeriformes and Psittaciformes, with low and high rates of chromosomal rearrangements, respectively, we can speculate about the importance of these sequence in the karyotype reorganization and the diversification of these clades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its unique life cycle quality and ability to switch from harmless normal flora microbiota to plaguing pathogen, C. albicans has become a point of interest in genome biology models and studies [ 39 ]. Recent studies have determined that the telomeric structure of C. albicans contributes to its pathogenicity and adaptability, while also contributing to the genetic biodiversity of these organisms [ 40 , 41 ].…”
Section: Candida Albicansmentioning
confidence: 99%
“…DNA recombination mediated by direct repeats (DR), a typical type of DNA repetition in which two copies of identical or highly similar sequences are arranged in the same orientation along a DNA strand, has been increasingly reported not only in prokaryotes but also in eukaryotes, making it clear that it may be a common genetic and evolutionary mechanism [ 24 , 25 , 26 ]. Several studies have shown that recombination may occur between DR regions in the chromosome or plasmids of Escherichia coli , further manifesting that the existence of DR might increase the possibility of the formation of various products of recombination [ 26 , 27 , 28 , 29 ]. Therefore, the role of DR-mediated recombination in the transmission of ARGs should not be neglected.…”
Section: Introductionmentioning
confidence: 99%